Genetic parameters in the interpopulation maize cross BR-105 x BR-106 and their implications in selection - Junior, Cláudio L. Souza; dos Santos, Manoel Xavier; Magnavaca, Ricardo; e Gama, Elto Eugenio Gomes (Pesquisa Agropecuaria Brasileira, 1993)
The genetic potential of two maize (Zea mays L.) populations BR-105 and BR-106 was evaluated for interpopulation improvement. Half-sib interpopulation progenies were evaluated at three locations: Sete Lagoas, MG, Goiânia, GO and Londrina, PR in Brazil. The estimate of the heterosis for ear weight was 19,23% and 17,86% in relation to the parental means and best parent, respectively. The additive x location interaction variance was 2,49 times superior to the additive genetic variance. The genetic variability was considered sufficient to permit selection progress for a large region because the estimated progress from reciprocal recurrent selection was 7,69%. The expected yield of the best hybrids were 25% and 33% superior to the yield of the interpopulation hybrid, before and after two cycles of selection, respectively. The results indicated that these populations have a good potential for use in breeding programs for reciprocal recurrent selection and production of inbred lines.